Approaches for Transformative Health Systems in Latin America - Sáenz Madrigal, María del Rocío (2025)
The presentation explores the adaptation of the SCIROCCO model to Latin American health systems, emphasizing the need for contextualized approaches to integrated care. It highlights the complexity and diversity of regional health structures and proposes a framework that incorporates transformational leadership, participatory governance, and systemic thinking. The model is reinterpreted to reflect person-, family-, and community-centered care, with a strong focus on equity, continuous training, and adaptive strategies. The goal is to guide the scaling of integrated care through locally grounded diagnostics, interdisciplinary collaboration, and culturally relevant policy development.